COVID-19-related mortality in kidney transplant and haemodialysis patients: a comparative, prospective registry-based study. Issue 11 (16th June 2021) - Goffin, Eric; Candellier, Alexandre; Vart, Priya; Noordzij, Marlies; Arnol, Miha; Covic, Adrian; Lentini, Paolo; Malik, Shafi; Reichert, Louis J; Sever, Mehmet S; Watschinger, Bruno; Jager, Kitty J; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) has exposed haemodialysis (HD) patients and kidney transplant (KT) recipients to an unprecedented life-threatening infectious disease, raising concerns about kidney replacement therapy (KRT) strategy during the pandemic. This study investigated the association of the type of KRT with COVID-19 severity, adjusting for differences in individual characteristics. Methods: Data on KT recipients and HD patients diagnosed with COVID-19 between 1 February 2020 and 1 December 2020 were retrieved from the European Renal Association COVID-19 Database. Cox regression models adjusted for age, sex, frailty and comorbidities were used to estimate hazard ratios (HRs) for 28-day mortality risk in all patients and in the subsets that were tested because of symptoms. Results: A total of 1670 patients (496 functional KT and 1174 HD) were included; 16.9% of KT and 23.9% of HD patients died within 28 days of presentation. The unadjusted 28-day mortality risk was 33% lower in KT recipients compared with HD patients HR 0.67 [95% confidence interval (CI) 0.52–0.85]. In a fully adjusted model, the risk was 78% higher in KT recipients [HR 1.78 (95% CI 1.22–2.61)] compared with HD patients. This association was similar in patients tested because of symptoms [fully adjusted model HR 2.00 (95% CI 1.31–3.06)]. This risk was dramatically increased during the first post-transplant year. Results were similar for other endpoints (e.g. hospitalization, intensive care unit admission and mortality >28 days) and across subgroups. Conclusions: KT recipients had a greater risk of a more severe course of COVID-19 compared with HD patients, therefore they require specific infection mitigation strategies.